Direct energy harvesting from starch by hybrid enzymatic and non-enzymatic cascade bioanode. Issue 31 (11th March 2016) - Wang, Zonghua; Xia, Lin; Xia, Jianfei; An, Zhendong; Gong, Shida
Abstract : A hybrid anode integrating enzymatic hydrolysis of starch by glucoamylase and non-enzymatic oxidation of glucose by gold nanoparticles is presented to achieve an efficient cascade energy conversion from starch. Abstract : A hybrid anode integrating enzymatic hydrolysis of starch by glucoamylase and non-enzymatic oxidation of glucose by gold nanoparticles is presented to achieve an efficient cascade energy conversion from starch. The as-prepared biofuel cell shows a maximum power output of 91.4 μW cm −2 . This enzymatic/non-enzymatic hybrid strategy can be employed to develop other polysaccharide or oligosaccharide fuel cells in which glucose oxidation is involved.